Starvation tactics using natural compounds for advanced cancers: pharmacodynamics, clinical efficacy, and predictive biomarkers. (6th May 2018) - El Bairi, Khalid; Amrani, Mariam; Afqir, Said
Abstract: The high mortality associated with oncological diseases is mostly due to tumors in advanced stages, and their management is a major challenge in modern oncology. Angiogenesis is a defined hallmark of cancer and predisposes to metastatic invasion and dissemination and is therefore an important druggable target for cancer drug discovery. Recently, because of drug resistance and poor prognosis, new anticancer drugs from natural sources targeting tumor vessels have attracted more attention and have been used in several randomized and controlled clinical trials as therapeutic options. Here, we outline and discuss potential natural compounds as salvage treatment for advanced cancers from recent and ongoing clinical trials and real‐world studies. We also discuss predictive biomarkers for patients' selection to optimize the use of these potential anticancer drugs. Abstract : Management of some metastatic cancers is a challenging area in clinical practice. Targeting tumor vessels is a promising strategy for cancer drug discovery. Natural compounds are an important source for finding new anticancer drugs targeting tumor vessels. Several randomized clinical trials have provided evidence for using natural compounds as a therapeutic option beyond first line and emerging data for their optimal use based on predictive biomarkers.